Dynamism with Incommensurate development: The distinctive Indian model - Lamba, Rohit and Subramanian Arvind (The Journal of Economic Perspectives)
India's sequencing of economic and political development has been unusual. In contrast to the West and more recently East Asia, democratization has preceded economic growth. Notwithstanding its unique path, India has grown substantially over the last four decades, pulling hundreds of millions out of poverty. The pace, durability, and stability of economic growth has been matched by few countries in the post-war period. This dynamism, though, has not been matched by development in several dimensions: a structural transformation that has skipped high-productivity manufacturing despite surplus labor, an increased spatial divergence in income despite integration in internal markets, limited convergence in education and other social metrics across castes but divergence across religions, a deep societal preference for sons that is associated with poor outcomes for women and high levels of stunting amongst children, and an environmental degradation that is severe for its level of income. The paper speculates on two immediate challenges: reviving dynamism when human capital development remains weak and the financial system is impaired and accelerating development when state capacity remains limited.